2010
DOI: 10.1007/s11845-010-0646-4
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponins: a potential treatment option for systemic lupus erythematosus

Abstract: While the exact cause of systemic lupus erythematosus (SLE) is still unknown, modern medicine has a number of effective treatments for this complex disorder. Corticosteroid hormones help reduce inflammation, antimalarial treatments address flare-ups and immunosuppressive medications work to keep the immune system in check. All these therapies are well tolerated, but accompany an increased risk of infection and nephrotoxicity. Recently, several studies showed that a number of natural and herbal products may als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Bioactive compound extracts from natural products are known to possess some therapeutic potential for inflammation (9)(10)(11)(12). Saikosaponin a (SSNa) is one of the major triterpenoid saponins derived from Bupleurum falcatum L. (13), and has various pharmacological activities such as anti-inflammatory, immunoregulating, antibacterial, antiviral, and anticancer activities (9,14-18).…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compound extracts from natural products are known to possess some therapeutic potential for inflammation (9)(10)(11)(12). Saikosaponin a (SSNa) is one of the major triterpenoid saponins derived from Bupleurum falcatum L. (13), and has various pharmacological activities such as anti-inflammatory, immunoregulating, antibacterial, antiviral, and anticancer activities (9,14-18).…”
Section: Introductionmentioning
confidence: 99%
“…SSs are also regarded as the major effective components of xiao-chai-hu-tang, one of the most popular Chinese medicinal formulae that has been widely used for its various pharmacological effects, including anti-inflammatory, antioxidant and antihepatic fibrosis properties (4-6). Thus far, at least 10 types of SS have been identified, and among which saikosaponin-d (SSd) is considered to be the most active component (1,7). Studies have reported that SS may potently inhibit the proliferation of hepatocellular carcinoma (8), cervical cancer (9), lung adenocarcinoma (10), colon carcinoma (11), breast cancer (12) and melanoma (13) cells.…”
Section: Introductionmentioning
confidence: 99%
“…As major bioactive compounds isolated from RB, saikosaponins have numerous biological activities, including immunoregulatory, anti-inflammatory, anti-bacterial and anti-viral activity (3,4). One study demonstrated that saikosaponin A (SSA) exhibits anti-inflammatory activity (5).…”
Section: Introductionmentioning
confidence: 99%